Intellectual Capital and Challenges of Organizations in the Twenty-First Century - Muhammad, Khalique; Shazali, Abu Mansor; Abu Hassan, Md. Isa; Jamal Abdul Nassir, bin Shaari (IGI Global, 2013)
In the present century, intellectual capital is recognized as the most important and strategic asset for organizations. Intellectual capital is mainly based on knowledge and useful information. Intellectual capital is playing a critical role to create value from the combination of tangible and intangible assets to enhance the performance of organizations. This chapterlooks at the concept and application of intellectual capital and its associated challenges of organizations in a competitive environment.